SAT0340 Psa-disk, a novel visual instrument to assess the burden of disease in psoriatic arthritis patients. (12th June 2018) - Chimenti, M.S.; Esposito, M.; Teoli, M.; Graceffa, D.; Peluso, G.; Birra, D.; Moretta, G.; Galossi, A.; Carboni, V.; Sensi, F.; Mazzotta, A.; Urbani, S.; et al.
Abstract : Background: The assessment of joint disease in psoriasis (PsO) patients is paramount, particularly where consensus among dermatology and rheumatology specialists is necessary. Objectives: To evaluate the prevalence of psoriatic arthritis (PsA) in PsO patients and assess how a novel 16-item visual instrument (PsA-Disk) correlates with the disease and its clinical manifestations. Methods: Data were prospectively collected from 8 dermatological/rheumatological centres across Italy. During their first dermatological visit, patients completed both PEST (Psoriasis Epidemiology Screening Tool) and PsA-disk questionnaires. Rheumatological visit was performed in order to confirm presence/absence of PsA. Clinimetric and disease activity variables were recorded. Results: From a total of 239 PsO patients, 120 (50.2%) patients were diagnosed with PsA. More PsA-positive patients had nail PsO (54.2% vs. 42%, p=0.05) and a PEST score ≥3 vs. PsA-negative patients (77.5% vs. 37.8%, p<0.001). PsA-positive patients presented with significantly higher ESR (21.9±17.1 vs. 15.9±10.2 mm/h, p=0.041), NAPSI-feet (10.2±9.7 vs. 3.9±7.8, p=0.002), NAPSI-(hands+feet; 9.3±6.8 vs. 4.6±7.9, p=0.007), and PsA-Disk scores (73.9±32.1 vs. 58.1±39.8, p<0.001) vs. PsA-negative patients. PsA-patients with axial involvement had higher PsA-Disk scores (86.7 vs. 72.5, p=0.088) as well as patients with knee arthritis (98.4 vs. 71.5, p=0.006). PsA-Disk scores were also positively correlated with number of swollen (r=0.2, p<0.05) and tender joints (r=0.24, p=0.021), patient- (r=0.4, p<0.001) and physician-pain-VAS (r=0.33, p<0.001), PGA-VAS (r=0.23, p=0.025), physician-HAQ (r=0.38, p=0.011), DAS-44 (r=0.25, p=0.023) and DAPSA scores (r=0.31, p=0.005) (figure 1A). Examples of the powerful visual use of this instrument can be seen in figure 1B. Conclusions: PsA-Disk is a novel instrument helping both dermatologist and rheumatologist in the rapid assessment PsA, facilitating in the timely therapeutic management of these patients. Disclosure of Interest: None declared